Elphick, Richard, The Equality of Believers. Protestant Missionaries and the Racial Politics of South Africa - J. J. Kritzinger (Acta Theologica)
From text: This book is a major contribution to the political and religious history of South Africa. Although its focus is on the years of Protestant missionary endeavours since the beginning of the 19th century up to about 1960, the subject of the book is inbedded in the whole colonial history since 1652 when the question of the relations between the races became an issue. It is the result of decades of intense, informed and fair scholarship (as its 30 pages Bibliography and 60 pages of Notes show). It gives not only a strong line of argument on the expressed theme, but also provides a wealth of (to me, at least) previous less known details about some of the main actors who played a significant role in the shaping of present and past ideologies in South Africa. In that sense it can also almost serve as an encyclopaedia, a Who’s Who of the South African racial debate (for which the 21 page Index is of great value).